Information and brain - Kycia, Radosław (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2021)
We present the consequences of the assumption of the classical and quantum nature of information storing and processing in the brain. These assumptions result in different behaviours of consciousness under a hypothetical brain copy experiment. The subject is important in the context of ‘mind uploading’ considerations.